Ecological Study of an Artificial Saline Lake Ecosystem in Wadi Al-Shatti, Libya - Elssaidi, Mohamed A. (Scientific Journal for Faculty of Science-Sirte University, 2022)
This study provided the first data related to the ecosystem of Ain Al-Mashashiya Lake. It is likely the new apperance of a saline artificial lake formed from agricultural drainage water from surounded local farms, small lakes provide an opportunity to understand intra-ecosystem connectivity and its dynamics. Water samples were collected representing two stations along edges and at the middle of the lake and other samples surrounded soil and vegetation. Lake depth was > 5 meters, the pH was found to be relatively high at edge of the lake (7.46 & 7.44) compared to at middle of the lake (7.38 & 7.32). Highly saline water, i.e., 129.79 & 125.48 dS/m & 126.82 & 133.74 dS/m at edge and middle of the lake respectively. The average level of PO4 and NO3 during winter is slightly lower than summer. The water cations abundances were typically Na > K > Ca > Mg, where were for anions, Cl > SO4 > HCO3 > PO4 > NO3. The lake is valuable for biodiversity and provide habitat for many species. Five phytoplankton types have been registered, i.e., Cocconeis, Notholca Pandorina, Oscillatoria, Chlamydomonas. The most common species were Pandorina & Oscillatoria. Soils of the study zone were classified as sandy loam, with a porosity of 44.53%. and saturated hydraulic conductivity (Ks) values was 4×10-3 cm/h and 6.4% of OM content. The soil reaction (pH) was 7.24 and its EC value was 19.42 dS/m that indicated high saline affected soil. The concentrations of Na, Ca & Mg, were as high as 193, 48 & 14.4 mg/kg, respectively, with low NO3 content 0.293 mg/kg. Tamarix (Tamarix aphylla) commonly found along the lake edges. The dry desert climate of the area played a main role in imposing the lake ecosystems.